The Role of Education of Islamic Education Institutions on Religious Moderation in The Community of Perbutulan Village, Sub-District, Sumber, Cirebon District - Al Qolbi, Labisal Fitri (Devotion : Journal of Research and Community Service, 2019)
Islamic educational institutions are places that can help people instill and develop Islamic teachings and values. In Islamic teachings, there is a teaching of moderatism that teaches a middle position or can be said to be not fanatical or excessive in thinking and acting. The education of Islamic education institutions in the village of Perbutulan plays a role in moderate religious education, influencing changes in social and religious behavior in community life as well as on priority fiqh problems that exist in the kelurahan of perutulan. As well as the role of Islamic education institutions in the attitudes of the people of the kelurahanperutulan towards differences in views between fellow Islamic educational institutions. The method used in this research is descriptive qualitative method by collecting data through interviews with those involved in Islamic education institutions and filling out online questionnaires to the community per month. The role of Islamic education institutions in the kelurahan towards religious moderation is as an introduction that in religion one has to respect one another, practice religion according to the guidance of the Al-Qur'an and the Sunnah. The Forestry Society does not argue over the differences between fiqh that exist in the community perutulan. with the existence of Islamic education institutions in perutulan can help people in carrying out daily life with religious knowledge that has been taught.